2010
DOI: 10.1002/cctc.201000001
|View full text |Cite
|
Sign up to set email alerts
|

Gas‐Phase Selective Oxidation of Benzyl Alcohol to Benzaldehyde with Molecular Oxygen over Unsupported Nanoporous Gold

Abstract: Dealloyed forces: Nanoporous gold, made by selective etching of Ag–Au alloys, exhibits extraordinary catalytic activity towards the gas‐phase oxidation of benzyl alcohol to form benzaldehyde with selectivities up to 98.2 %, using molecular oxygen as an oxidant under relatively low‐temperature conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 29 publications
2
45
0
Order By: Relevance
“…4). Similar results were also reported while the NaOH pretreated NPG catalysts were applied for the gas-phase oxidation of benzyl alcohol [40]. Therefore, the enhancement of catalytic activity might be determined by the amounts of OH groups introduced within NPG upon alkaline treatment, which was closely related with the concentration of alkaline solution and immersing time.…”
Section: Resultssupporting
confidence: 75%
“…4). Similar results were also reported while the NaOH pretreated NPG catalysts were applied for the gas-phase oxidation of benzyl alcohol [40]. Therefore, the enhancement of catalytic activity might be determined by the amounts of OH groups introduced within NPG upon alkaline treatment, which was closely related with the concentration of alkaline solution and immersing time.…”
Section: Resultssupporting
confidence: 75%
“…92 In 2010, Ding et al also reported that larger alcohols, such as benzyl alcohol, can be selectively oxidized using npAu catalysts and O 2 as the oxidant. 98 The main product was the industrially important benzaldehyde; in all cases, the selectivity of the conversion was above 92%; the conversion started at temperatures slightly above 200°C and already at 240°C, the conversion was close to 60%, showing a remarkable activity (turnover frequency of ∼1.4 s −1 ).…”
Section: Catalysis By Nanoporous Goldmentioning
confidence: 99%
“…Selective oxidation of benzyl alcohol has been investigated in both the vapor and liquid phases [6]. While liquid-phase oxidations are generally carried out below 100°C, vapor phase oxidations with molecular oxygen generally require temperatures above 200°C, the boiling point of benzyl alcohol being 203°C [7].…”
Section: Introductionmentioning
confidence: 99%